Dampak Kematangan TI Organisasi pada Proses Alignment Bisnis dengan TI - Firdaus -; Adri Praharja; Tri Hasmoro (Universitas Sriwijaya, 2009)
IT maturity is decided by making the IT goal compatible with and the general purpose of the organization and explaining its role. IT maturity level can be classified in 3 level; Systems to automate process (DP), Systems to aid decision making (MIS), Strategic systems (SIS). The maturity is affected by many variables which some of the variables are included in four main categories; contextual aspects and strategy, IT department, Computer System, and the character of basic application. IT maturity in organization has big impact in the alignment process between IT and organization business purpose. This impact can be measured its effect on criteria that becomes the business alignment parameter and IT. Criteria are mapped to see theconnection between IT maturity and business -IT alignment process. This is presented in form of table showing the connection between the factors that affect the alignment process and IT maturity Kata kunci : kematangan TI, proses penyelarasan bisnis-TI.